Connect your LAN to the Internet cost-effective access for small businesses and other organizations - Madron, Thomas William 1937- (John Wiley & Sons, 1996)
The ultimate do-it-yourself guide to getting your LAN on the InternetMore and more small to mid-size businesses are waking up to the fact that, in today's global marketplace, you've got to be on the Internet if you want to stay competitive. But connecting your Local Area Network to the Net can be like trying to cross a minefield on a skateboard. If you are the ad hoc network administrator at your company and have been charged with that task, here's the do-it-yourself book you've been praying for. It tells you everything you need to know to link your LAN to an Internet service provider and supply everyone on your network with the full range of Internet services-quickly, cheaply, and securely. Concentrating on cost-effective strategies for getting your LAN on the Net, author Thomas Madron: Shows you all the technical basics of connecting to the Internet Helps you decide what your company actually needs and doesn't need Tells you how to find and use software and tools available in shareware or freeware Describes the advantages, disadvantages, and varying installation procedures for the major Internet servers, including Linux and Windows NT Walks you step-by-step through the entire connection processFind out how to bring full Internet capabilities to your organization's computing network with Connect Your LAN to the Internet.